What’s In The Name Of Management Consultancies? How Celebrity And Reputation Shape Intervention Effectiveness - Fink, Dietmar; Knoblach, Bianka (Journal of Applied Business Research, 2017)
This study contributes to the growing body of research concerning management consultancies by linking two previously disparate fields of study: (1) the examination of the effectiveness of consulting interventions and (2) the examination of the social processes that aim to create and legitimize the insights, knowledge and capabilities of management consultancies. We propose that consulting firms accumulate social authority in the course of preintervention discourse processes that is reflected in their reputation and celebrity. With respect to intervention, this social authority affects change recipients’ commitment to and compliance with the requirements of change implementation. We test the proposed relationships by conducting a measured variable path analysis of 117 change initiatives in German companies that were set up and implemented with the assistance of external consultancies. Our findings indicate that a consulting firm’s levels of both celebrity and reputation affect the change recipients’ commitment to proposed change strategies and thus, indirectly affect their behavioral compliance with the explicit requirements of change implementation.
Keywords: Management Consulting; Intervention; Reputation; Commitment